Effect of Cr2O3 - Al2O3 Composite Film on the High Temperature Oxidation Resistance of 304 Stainless Steel - MA Jing, WANG Rui - yang, WEN Ning, LI Jian - hui, WANG Jian - gang (Cailiao Baohu)
Oxide film obtained by electrodeposition - pyrolysis method is an important way to improve the high temperature oxidation resistance of materials. In this work, single and composite Cr2O3 - Al2O3 films were prepared on 304 stainless steel by electrodeposition - pyrolysis with different electrolyte concentration, and the single film and composite films prepared with different concentration solution were tested to study their cyclic oxidation behaviors at 900 ℃. The oxidation kinetics curve, SEM morphology and XRD analysis showed that oxide film deposited by electrodeposition - pyrolysis improved the high temperature oxidation resistance of 304 stainless steel obviously. Protective Cr1.3Fe0.7O3 and NiCr2O4 oxide scales were formed after high temperature oxidation on the surface of Cr2O3 - Al2O3 composite films, which were prepared in Cr(NO3)3 and Al(NO3)3 alcohol solution with the mole ratio of 2∶1. The as - prepared films possessed the optimal high temperature oxidation resistance, and their oxidation weight gain and oxide film peeling amount were 27.32% and 17.62% of those without deposition film, respectively. Moreover, the composite film reduced the partial pressure of oxygen on the surface of the alloy, which was favor to the formation of protective selective oxide films. Both Cr2O3 and Al2O3 had excellent oxidation resistance, and owing to Al2O3 reducing the volatilization of Cr2O3 at high temperature, the high temperature oxidation resistance of composite film was significantly improved.